2014
DOI: 10.1111/hae.12514
|View full text |Cite
|
Sign up to set email alerts
|

Genetic background and risk of postpartum haemorrhage: results from an Italian cohort of 3219 women

Abstract: Postpartum haemorrhage (PPH) is a leading cause of maternal mortality, particularly in the developing countries, and of severe maternal morbidity worldwide. To investigate the impact of genetic influences on postpartum haemorrhage, in association with maternal and intrapartum risk factors, using a candidate gene approach. All women (n = 6694) who underwent a vaginal delivery at the Obstetric Unit of a large University hospital in Milan (Italy) between July 2007 and September 2009 were enrolled. The first conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…In an Italian study of 3,219 women with postpartum hemorrhage, the alternate allele was associated with postpartum hemorrhage compared with controls (OR: 0.79, CI: 0.69-0.90). 55 Mechanistic studies have shown that rs1361600 decreases promoter activity and constitutive expression of F3, 45,47 consistent with the proposed mechanism for rs1361600 in postpartum hemorrhage. Furthermore, the effects of rs1361600 vary by tissue type as detailed later.…”
Section: Targeted Clinical Investigation Of Human F3 Snpssupporting
confidence: 67%
“…In an Italian study of 3,219 women with postpartum hemorrhage, the alternate allele was associated with postpartum hemorrhage compared with controls (OR: 0.79, CI: 0.69-0.90). 55 Mechanistic studies have shown that rs1361600 decreases promoter activity and constitutive expression of F3, 45,47 consistent with the proposed mechanism for rs1361600 in postpartum hemorrhage. Furthermore, the effects of rs1361600 vary by tissue type as detailed later.…”
Section: Targeted Clinical Investigation Of Human F3 Snpssupporting
confidence: 67%
“…The association between genetic disorders of GP1BA and Bernard-Soulier syndrome (also known as giant platelet syndrome), which is characterized by a low platelet count and giant platelets, has been reported in Iranian, Indian and Kuwaiti populations, even though the gene variants or frameshifts are located in different regions of the GP1BA sequence (27)(28)(29)(30). Furthermore, a GP1BA polymorphism has been associated with post-partum hemorrhage (31). In the present study, the same deletion of the GP1BA gene [c.1322_1344del23, p.Ser441TyrfsTer (frameshift and termination), rs770089708] was detected in the proband and the proband's sister.…”
Section: Resultsmentioning
confidence: 99%
“…Biological differences may influence the effect of race or ethnicity disparities on PPH. A previous study attempting to identify genetic background that influences the PPH reported that the gene polymorphism carries a protective effect against PPH [ 45 ]. Because PPH incidence depends on various factors; genetic predisposition such as a defect in coagulation or tissue elasticity might also lead to higher PPH incidence in different races or ethnicities [ 46 ].…”
Section: Discussionmentioning
confidence: 99%